Recent Advances in Metal-Organic Framework-Based Electrochemical Biosensing Applications - Li, Mengjie; Zhang, Guangyao; Boakye, Andrews; Chai, Huining; Qu, Lijun; Zhang, Xueji (Frontiers in Bioengineering and Biotechnology, 2021)
In the face of complex environments, considerable effort has been made to accomplish sensitive, accurate and highly-effective detection of target analytes. Given the versatility of metal clusters and ligands, high porosity and large specific surface area, metal–organic framework (MOF) provides researchers with prospective solutions for the construction of biosensing platforms. Combined with the benefits of electrochemistry method such as fast response, low cost and simple operation, the untapped applications of MOF for biosensors are worthy to be exploited. Therefore, this review briefly summarizes the preparation methods of electroactive MOF, including synthesize with electroactive ligands/metal ions, functionalization of MOF with biomolecules and modification for MOF composites. Moreover, recent biosensing applications are highlighted in terms of small biomolecules, biomacromolecules, and pathogenic cells. We conclude with a discussion of future challenges and prospects in the field. It aims to offer researchers inspiration to address the issues appropriately in further investigations.